(untitled) (Al-Aasar, 2025)
In the field of Qur’anic understanding, two eminent exegetes of the Indian subcontinent – Maulana Ubaidullah Sindhi and Maulana Amin Ahsan Islahi –hold a prominent position. Both of them presented the interpretation of the Qur’an with a systematic intellectual methodology; however, there is a clear difference in their perspectives and principles of exegesis.Maulana Ubaidullah Sindhi’s exegesis, “Al-Maqam Al-Mahmood,” is in fact part of his broader intellectual system, which he presented as a continuation of Shah Waliullah’s socio-political thought. His tafsir distinctly reflects Shah Waliullah’s wisdom, the formulation of a collective social system, the principles of an Islamic state, and the practical dimensions of the Qur’an. His methodology is predominantly referred to as socio-political exegesis, in which the verses are not confined merely to spiritual or individual guidance but are used to derive a collective revolutionary manifesto.In contrast, Maulana Amin Ahsan Islahi, in his exegesis “Tadabbur-e-Qur’an,” based his approach on the principles of Qur’anic coherence (Nazm) established by his teacher Imam Hamiduddin Farahi. According to him, the Qur’an is a coherent and systematic book in which each surah has a central theme, and the interrelation and connection between surahs provide consistent guidance. His methodology is grounded in literary, principled, and semantic coherence, where the arrangement of verses and surahs, the precedence and delay of words, and the context are used to present a rational and well-structured interpretation.